Parsing Model and a Rational Theory of Memory - Dotlačil, Jakub; de Haan, Puck (Frontiers in Psychology, 2021)
This paper explores how the rational theory of memory summarized in Anderson (1991) can inform the computational psycholinguistic models of human parsing. It is shown that transition-based parsing is particularly suitable to be combined with Anderson's theory of memory systems. The combination of the rational theory of memory with the transition-based parsers results in a model of sentence processing that is data-driven and can be embedded in the cognitive architecture Adaptive Control of Thought-Rational (ACT-R) (Anderson et al., 2004). The predictions of the parser are tested against qualitative data (garden-path sentences) and a self-paced reading corpus (Futrell et al., 2018).